2018
DOI: 10.1111/jdv.14998
|View full text |Cite
|
Sign up to set email alerts
|

Acne and nutrition: hypotheses, myths and facts

Abstract: Acne is an inflammatory and multifactorial skin disease. Different external and internal factors, including air pollution, aggressive skincare products, medication, mechanical, hormonal and familial factors and, more recently, lifestyle and stress, have been suggested as having an impact on acne. Moreover, for many years nutrition was believed to cause or worsen acne. Over the last decades, however, it has become a dermatological doctrine that there is no direct association between diet and acne. Even if recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 110 publications
(221 reference statements)
1
43
0
1
Order By: Relevance
“…An association between diet and acne has been hypothesized for decades. The epidemiological studies have shown that the incidence of acne is significantly lower in non-industrialized societies than in westernized populations [150]. For example, acne is extremely rare among the Inuit, Okinawan, and Kitavian Islanders, and Ache hunter-gatherers.…”
Section: Acne and Pufasmentioning
confidence: 99%
“…An association between diet and acne has been hypothesized for decades. The epidemiological studies have shown that the incidence of acne is significantly lower in non-industrialized societies than in westernized populations [150]. For example, acne is extremely rare among the Inuit, Okinawan, and Kitavian Islanders, and Ache hunter-gatherers.…”
Section: Acne and Pufasmentioning
confidence: 99%
“…Consequently, onychomatricoma is often misdiagnosed as onychomycosis, which deprives the patient of appropriate treatment for onychomatricoma. 2 A 47-year-old man presented with a thickened and yellowish right hallux toenail for 5 years (Fig. 1a).…”
Section: A Case Of Veiled Onychomatricomamentioning
confidence: 99%
“…In these studies, the relationship between glycemic index-based food con- sumption and AV has been investigated mostly regarding fish meat, milk/dairy products, and chocolate. [20][21][22] There are conflicting results in different studies on the effect of BMI on AV development as in certain other skin diseases. [23][24][25][26] In this study, there is no statistically significant difference in mean BMI between the patients with AV and the control group.…”
Section: Discussionmentioning
confidence: 99%